Polish language as the main factor to continue Polish national identity in South Bukovina since the second half of the 18th century - Drzewiecka, Aleksandra (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
The Polish minority has been in Southern Bukovina for many generations. To this day, there are Polish cultural and educational organizations, minority members eagerly practice Polish traditions and national customs. The main factor that created opportunities for the development of Polish national identity was the Polish language. The language has been passed down to the next generations and is still used today. The first Poles after the settlement of Bukovina could open a Polish church, schools and social organizations, as a resolute Polish was used by many people and in many places, and became popularized. Subsequent activities of the Polish minority developed interpersonal relationships among the minorities. The Polish language united all Poles in Bukovina, developed institutions and ties with their homeland. The Polish minority continues to practice the Polish language over 200 years after the arrival of their ancestors, as a result Polish identity still exists today. The method of analysis was used in the article. Activities that popularized learning the Polish language and opportunities to promote tradition and identity were presented. Also the history of the southern territory of Bukovina and its impact on the development of the Polish national minority.